Конструктивні особливості технічних засобів для відбору керна в горизонтальних свердловинах - Кунцяк, Я.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2012)
В даній статті подано розроблені вимоги до конструкцій керноприймальних пристроїв для відбору керна в похило-скерованих і горизонтальних свердловинах. Приведено результати експериментальних і промислових досліджень удосконаленої конструкції кулькової підвіски, призначеної для відбору керна у свердловинах з великими зенітними кутами викривлення, нових конструкцій важільців та пружинок керновідривачів і технологію їх виготовлення. В настоящей работе представлены разработанные требования к конструкциям керноприёмных приспособлений для отбора керна в наклонных и горизонтальных скважинах. Приведены результаты экспериментальных и промысловых исследований усовершенствованной конструкции шаровой подвески, предназначенной для отбора керна в скважинах с большими зенитными углами искривления, новых конструкций важильков и пружинок керноотрывателей и технологию их изготовления. This thesis contemplates the forecast issue by numerical method, based on up-to-date computer technology, behavior of weighted drill pipes structures of variable stiffness, threaded tongue-grove joints of “fillet type” and bottomhole assembly during their loading under operating conditions, beyond linear deformation, taking into account the existing methods of mathematical modeling. Factoring into the external force applied to drill string parts, which determines their behavior by nonlinear laws, the thesis also considers the problem of defining strength characteristics and forecasting operational capability of structures, obtaining cracks at the line between material plasticity and nonlinear deformation. The paper has sketches of weighted drill pipes structures of variable stiffness and threaded tongue-groove joints of “fillet type”, for which, in exemplification, such mathematical methods were searched, that could lead to the most actual results in terms of up-to-date computer technology, in order to assess forecast of service life and operating capability of drill string parts. This thesis includes comparative interactive curves, received in the course of experimental investigation of full-scale specimens and computer programs, developed using mostly suitable mathematical models for every case.